The 'worst of the worst': punitive justice frames in criminal sentencing clips on YouTube. Issue 4 (2nd October 2021) - Revier, Kevin
ABSTRACT: Courtroom media is a longstanding genre of news and entertainment, in radio, film, television, and print. Digital streaming platforms such as YouTube, which boasts over 2 billion users, have become a prominent source of courtroom content. In this research, I examine popularized YouTube sentencing clips: fairly short videos (often no more than a few minutes) which generally include a sentence-reaction formula, have little context (case, social, or individual), and are digitally shared, edited, and distributed online, primarily by news outlets and private channels. Specifically, I conduct a frame analysis of 53 sentencing clips from United States' courtrooms. I find that sentencing clips reinforce dominant punitive justice frames, including justice-as-retribution, justice-as-victim-advocacy, and justice-as-entertainment. Moreover, as the majority of clips feature defendants sentenced for violent acts, including sexual assault, murder, and child abuse, they depict the 'worst of the worst' being brought to justice. Thus, in a time of criminal justice reform, of which there has been popular concern regarding the 'relatively innocent, ' the criminal bogeyman remains alive and well on digital media platforms like YouTube. Punitive frames associated with the 'worst of the worst, ' in turn, reinforce a punishment paradigm constitutive of contemporary U.S. criminal justice as a whole.